2016
DOI: 10.1007/s11356-016-7403-9
|View full text |Cite
|
Sign up to set email alerts
|

Export product diversification and the environmental Kuznets curve: evidence from Turkey

Abstract: Countries try to stabilize the demand for energy on one hand and sustain economic growth on other, but the worsening global warming and climate change problems have put pressure on them. This paper estimates the environmental Kuznets curve over the period 1971-2010 in Turkey both in the short and the long run. For this purpose, the unit root test with one structural break and the cointegration analysis with multiple endogenous structural breaks are used. The effects of energy consumption and export product div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(56 citation statements)
references
References 66 publications
(13 reference statements)
4
51
0
1
Order By: Relevance
“…Our results are in line with the findings of the other two studies (Apergis et al, ; Gozgor & Can, ). Gozgor and Can () found that, in the long run, greater export diversification across products generates higher CO 2 emissions for Turkey. In our sample, Turkey is an upper middle‐income economy and is therefore classified as a developing country.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results are in line with the findings of the other two studies (Apergis et al, ; Gozgor & Can, ). Gozgor and Can () found that, in the long run, greater export diversification across products generates higher CO 2 emissions for Turkey. In our sample, Turkey is an upper middle‐income economy and is therefore classified as a developing country.…”
Section: Discussionsupporting
confidence: 94%
“…Focusing now on export structure, numerous empirical studies show a robust inverted U‐shaped relationship between economic development and export diversification (Cadot et al, ; Cadot, Carrère, & Strauss‐Kahn, ; IMF, ; Klinger & Lederman, ). To measure export diversification, we choose to calculate the Theil index for every single country‐year observation because of its widespread use (Apergis et al, ; Cadot et al, , ; Can & Gozgor, ; Gozgor & Can, ; IMF, ; Shahbaz et al, ). The Theil index is a concentration index; consequently, it is inversely proportional to the degree of export diversification.…”
Section: Stylized Factsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of introducing Kuznets Curve of export diversification was originally proposed by Cadot [28]; however, his article was more focused on theory description without empirical analysis. In 2016, Gozgor tested the relationship between export product diversification and pollution based on data on Turkey from 1971 to 2010 using Kuznets curve empirically and came to the conclusion that higher export product diversification leads to more intensive CO 2 emissions [32]. Gozgor tested export product diversification, while export diversification includes both export market diversification and export product diversification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the rapid development of the science and technology of materials research, perovskites have received extensive attention 1 for their unique properties, such as stable structure, 2 electromagnetic characteristics, 3 thermal stability, 4 moderate price, widespread sources and gas sensitivity. In addition to the worsening environmental problems, [5][6][7][8][9][10][11][12] the air pollution due to particles is of concern. 13 Perovskites are sensitive to gas and act as gas sensing materials [14][15][16] that can adsorb and detect a very large number of poisonous gases, e.g., CO, NO x , SO 2 and VOCs.…”
Section: Introductionmentioning
confidence: 99%